Research in the social scientific study of religion. - Piedmont, Ralph L., 1958-; Village, Andrew. (Research in the Social Scientific Study of Religion, 2011)
Research in the Social Scientific Study of Religion publishes empirical and theoretical studies of religion from a wide range of disciplines and from all parts of the globe. A special section is devoted to the issue of psychological type and religion and especially how psychological type can increase our understanding of Christian ministry. Alongside this section are papers presenting studies on subjects such as civic participation, suffering with God, and spirituality. Together these papers represent important contributions that advance theory and evidence in a number of different fields of contemporary relevance to the study of religion.